Implementation of a Complementary and Integrative Medicine Service on a Palliative Care Unit of a Tertiary Care Center in Switzerland. - Werner, Kathrin; Feuz, Markus; Theile, Gudrun; Hertler, Caroline; Blum, David; Schettle, Markus (Journal of Palliative Medicine, 2026)
Background: Complementary therapies are gaining interest in palliative care. This study investigated the implementation of a complementary and integrative medicine (CIM) service on a palliative care unit of a Tertiary Care Center in Switzerland. Aim: This study aims to explore how health care professionals, patients, and family members perceive complementary medicine in specialized palliative care, identify related challenges and opportunities, and develop strategies for their effective and sustainable implementation into routine practice. Methods: In a first step, to check acceptability, in 2016, an interview study was carried out by conducting qualitative interviews with nurses, physicians and patients, and their relatives. In a second step, based on the results of the structured interviews, CIM experts developed complementary nursing interventions followed by an educational program and establishing CIM service on the ward. Results: Eight nurses, six doctors, four patients, and three relatives were interviewed. The interviews revealed a generally positive attitude among all stakeholders with high acceptability. Key challenges faced by medical staff included time management, training needs, and interdisciplinary communication. Patients and relatives emphasized the need for CIM to alleviate symptoms, improve quality of life, and enhance confidence in integrated care. The developed nursing interventions include selected measures (wraps/compresses and rhythmic embrocations) targeting common symptoms like pain, nausea, anxiety, and respiratory distress. To ensure quality control and sustainability, the concept also features an organizational framework, regular specialist training, and a detailed manual and accessible videos, along with guidelines for documentation and quality assurance. Conclusion: Medical professionals, patients, and relatives viewed the implementation of complementary nursing interventions as beneficial for enhancing symptom management in palliative care. Establishing appropriate framework conditions based on current implementation research is essential, and further research on effectiveness and long-term implementation is needed.